DIGITAL TECHNOLOGIES: HOW THEY ARE TRANSFORMING OUR LIVES - Yigitaliev Ruzimatjon (Web of Journals Publishing, 2024)
This article explores the profound impact of digital technologies on contemporary life, examining their role in reshaping society and individual experiences. It begins with an overview of digital technologies, emphasizing their historical evolution and global significance. The article then delves into specific areas of influence, including communication, commerce, education, healthcare, and entertainment. It discusses how technologies like artificial intelligence (AI), big data analytics, blockchain, and cryptocurrencies are revolutionizing various sectors. Additionally, the article addresses cybersecurity challenges and the implications for personal data protection. It concludes by exploring future trends and potential developments in the digital landscape, highlighting opportunities and challenges for innovation and societal advancement.
Keywords: Digital technologies, transformation, society, communication, commerce, education, healthcare, entertainment, artificial intelligence (AI), big data analytics, blockchain, cryptocurrencies, cybersecurity, personal data protection, innovation, future trends, global impact, challenges.